Readiness of Health Facilities in Providing Antenatal Care Laboratory Tests and Satisfaction of Clients in Ethiopia - Abawollo, Hailemariam Segni (Ethiopian Journal of Reproductive Health, 2022)
Abstract Background: For early identification of pregnancy complications and other problems that affect the outcomes of pregnancy, pregnant women need to receive laboratory tests during antenatal care. The provision of antenatal care laboratory tests is influenced by the availability and capacity of the support systems. Objective: The objective of this study is to assess the readiness of health facilities in providing antenatal care laboratory tests and satisfaction of clients. Methods: A health facility based cross-sectional study design was employed. Facility readiness was assessed in a sample of 205 health facilities and exit interview with 1,180 pregnant women. Results: 199 facilities and 960 pregnant women were involved. The sampled facilities have fulfilled the minimum requirements including 67% for infrastructure, 67.2% for documents, 49.6% for equipment, and 76% for trained laboratory personnel. The average reagents stockout rate on the date of the visit was 29.6% with stockouts during the past thirty days being at 32% and the mean number of days stocks last for 93 days. The average availability of the laboratory tests was 84% with infrastructure (p=0.018) and equipment (p=0.000) being the significant predictors. The overall satisfaction rate with the services provided was 83.2%. Conclusions: Readiness of health facilities to deliver antenatal care laboratory tests was low with acceptable client satisfaction rate. The identified gaps need to be addressed to ensure better quality antenatal care laboratory test services. Key words: Laboratory test, Antenatal care laboratory tests, ANC laboratory tests, USAID, Transform: Primary Health Care.